Work Environment, Discipline, and Stress as Determinants of Service Quality at Jangkang Community Health Center - Fansha Tio Anugrah; Sulastini Sulastini; Khuzaini Khuzaini (Sean Institute, 2026)
Quality in primary health services is essential for achieving Universal Health Coverage, particularly in rural areas where community health centers face geographical, organizational, and workforce constraints. This study examines the effects of work environment, work discipline, and work stress on service quality at Jangkang Community Health Center, Kapuas Regency, Central Kalimantan. A quantitative explanatory design was applied using a census sampling technique. Questionnaire responses from 45 employees were analyzed through multiple linear regression using SPSS version 27. The results show that work environment positively and significantly affects service quality (B = 0.782; p = 0.006), work discipline positively and significantly affects service quality (B = 0.669; p = 0.026), and work stress negatively and significantly affects service quality (B = -1.205; p = 0.000). Simultaneously, the three variables significantly explain service quality (F = 15.231; p = 0.000), with an Adjusted R Square of 0.492. The findings indicate that improving service quality requires adequate work conditions, consistent discipline practices, and structured stress-management support. Strengthening organizational support and employee well-being is therefore important for sustainable primary health service delivery.